Determinants of customer intention towards personal financing Aslah Tawarruq: A case study at Bank Rakyat in Pasir Mas / Nur Farah Syifaa’ Che Mainudin - Che Mainudin, Nur Farah Syifaa’ (2014)
The aim of this study is to examine the factors that influence customer intention towards personal financing Aslah Tawarruq at Bank Rakyat Pasir Mas. There are three factors that have been studied. The factors consist of corporate image, pricing, and attitude. In collecting the data, a researcher was used primary data. The questionnaire had been used in order to get feedback from customer. 100 questionnaires had been distributed and had gotten back 100 respondent’s feedback. The data collected was tested on its frequency analysis and further analyse by using reliability analysis, descriptive and regression analysis. Besides that, correlation was used to test the hypotheses in this study. The findings of this paper suggest that the corporate image, pricing, and attitude are significant factors in explaining customer intention towards personal financing Aslah Tawarruq. Based on the results obtained in this study, some suggested recommendations can help Bank Rakyat Pasir Mas to improve their image and also can attract more customers to apply personal financing Aslah Tawarruq.